2008
DOI: 10.1002/smll.200700997
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivation of CdSe/ZnS Quantum Dots Embedded in Silica Colloids

Abstract: A study of the influence of the local environment on the light-induced luminescence enhancement of CdSe/ZnS quantum dots (QD) embedded in silica colloids that are dispersed in various solvents is presented. The photoluminescence of the embedded QD is enhanced up to a factor of ten upon photoactivation by ultraviolet or visible light. This enhancement is strongly dependent on the local environment. The thickness-dependent permeability of the silica shell covering the QD controls the influence of the solvent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
67
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 49 publications
3
67
0
Order By: Relevance
“…40 Such photo-activation (photo-enhancement) of fluorescence has been observed in solutions of free QDs after exposure to sunlight, 41 UV radiation, 42 and blue light 43 or QDs embedded in silica colloids under UV radiation. 44 Normally, a decrease in QD fluorescence intensity occurs due to oxidative decay of the CdSe lattice in the presence of oxygen, while in nitrogen, photobleaching is absent. 45 Dembski et al 44 proposed that UV radiation generates excitons, which form O 2 − from the oxygen adsorbed on the surface of QDs: when irradiation stops, O 2 − dissociates, diminishing the oxygen passivation effect and thus decreasing QD fluorescence.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…40 Such photo-activation (photo-enhancement) of fluorescence has been observed in solutions of free QDs after exposure to sunlight, 41 UV radiation, 42 and blue light 43 or QDs embedded in silica colloids under UV radiation. 44 Normally, a decrease in QD fluorescence intensity occurs due to oxidative decay of the CdSe lattice in the presence of oxygen, while in nitrogen, photobleaching is absent. 45 Dembski et al 44 proposed that UV radiation generates excitons, which form O 2 − from the oxygen adsorbed on the surface of QDs: when irradiation stops, O 2 − dissociates, diminishing the oxygen passivation effect and thus decreasing QD fluorescence.…”
mentioning
confidence: 99%
“…44 Normally, a decrease in QD fluorescence intensity occurs due to oxidative decay of the CdSe lattice in the presence of oxygen, while in nitrogen, photobleaching is absent. 45 Dembski et al 44 proposed that UV radiation generates excitons, which form O 2 − from the oxygen adsorbed on the surface of QDs: when irradiation stops, O 2 − dissociates, diminishing the oxygen passivation effect and thus decreasing QD fluorescence. However, irradiation for a longer period will lead to oxidation of the QD surface and desorption of SeO 2 and SO 4 − , 44 accompanied by the release of Cd 2+ and Zn 2+ .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, increased photo-enhancement of QDs embedded in silica colloids have been reported in living cells, due to partial degradation mediated by oxidation with minimal aggregation. 46 Results suggested that Ps protect QDs from biological interactions in cell compartments, thus improving the quality of cellular imaging.…”
Section: 44mentioning
confidence: 99%